Implementasi Perma Nomor 01 Tahun 2008 Tentang Prosedur Mediasi Di Pengadilan Dalam Menyelesaikan Sengketa Perceraian(Studi Hukum Di Pengadilan Agama Surakarta) - Utomo, Dimas Bagus Prasetyo; , Darsono, SH, MH; , Shalman Alfarizi, SH, Mkn (2016)
Settlement of disputes in Surakarta Religious Court, dominated the divorce case. As the court of first instance in Surakarta, shall carry out the process of divorce mediation in resolving disputes. This is in accordance with mandated in Perma No.1 of 2008 on Mediation Procedure in court. The results of the study, noted that: Dispute resolution procedures of divorce in the Religious Surakarta, has been implemented in accordance PERMA No. 01, 2008. To provide a reference for the mediation Mediator Judge, Court of Surakarta Religion published Standard Operating Procedure (SOP) of the Case Resolution Through Mediation in Surakarta Religious Court. Mediation resulted in an agreement of the parties, in the end the divorce disputes through peace or not an agreement of the parties to the path of peace, so that the dispute should continue kesidang divorce court. Efforts have been made to improve the success of the mediation, is to increase the role of mediator in the mediation process and intervene with Islamic teaching approach in solving the case. Fact the field shows that resolve disputes through mediation divorce, is more difficult than with a settlement tothe case concerning the material. Keywords: Dispute divorce, failure of the mediation, the mediator's role and approach to Islam